TI_GERICHTE 52.2022.393 vom 26. Oktober 2022 , Procedimento amministrativo per infrazione alla LCPubb. Divieto di subappalto - TI Tribunale d'appello (2022)
Procedimento amministrativo per infrazione alla LCPubb. Divieto di subappalto